Interior partition walls in mediterranean climates: lightweight versus heavyweight - Mendonça, Paulo (2012)
The aim of this paper is to analyse the environmental and functional performance of interior partition wall technologies existing in Mediterranean climates, specifically on Portuguese territory. The evolution of interior partition walls, namely by the evolution of its weight, is presented and discussed. "Light-tech" bets on the introduction of more efficient systems by the weight reduction of constructive elements. This allows saving material and energetic resources, what constitutes a relevant response to the growing concerns over environmental issues and incertitude on economic development. But if lightweight solutions can be potentially interesting from the point of view of the environmental impacts associated with the production of materials, on the other hand it can be problematic from the point of view of the thermal comfort energetic demands. In a Mediterranean climate, the insufficient thermal inertia and acoustic insulation, due to the reduced mass of its constructive elements can constitute a severe problem. But thermal mass can be assured by slabs, exterior walls and in dwellings’ dividing walls. The functional problems associated with lightweight solutions are not as relevant in internal partitions. Apart from this, lightweight sandwich configurations can be used to increase thermal and acoustic insulation if the air gap between external finishing layers is filled by absorbent materials, such as rockwool. This paper focus on the advantages of the lightweight existing partition walls and it is expected that may contribute for the development of new partition wall technologies. The traditional lightweight solutions are compared with the conventional heavyweight solutions. The analysis shows that interior lightweight partition walls present lower environmental impacts than the heavyweight solutions.